Old Things - Wang, Lianghe, 1963- (Book collections on Project MUSE., 2019)
Drawn from Hong Kong International Poetry Nights 2011, Old Things is a chapbook of poetry by Wong Leung Wo presented in both English and Chinese. Old Things is also available along with the works of other internationally renowned poets in Words and the World (Twenty-volume Set). Selected poems from this volume are featured in the anthology Words and the World: International Poetry Nights in Hong Kong.